Hydrophilizing agent composition for metals

JP7668654B2Active Publication Date: 2025-04-25NIPPON SHOKUBAI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2021039587
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2025-04-25
Estimated Expiration
2041-03-11

AI Technical Summary

Technical Problem

Conventional hydrophilizing compositions for heat exchanger fins face issues such as heat resistance leading to discoloration of the coating film, poor film adhesion, and inadequate hydrophilization.

Method used

A metal hydrophilizing agent composition containing a poly(meth)acrylic acid-based polymer with 5 to 90 mol% of carboxyl groups neutralized by secondary or tertiary amines and a phosphorus content of 0.1 to 15% by mass, which enhances film adhesion and prevents discoloration.

Benefits of technology

The composition effectively hydrophilizes metal surfaces, ensuring excellent coating film adhesion and minimizing discoloration, making it suitable for fin materials in heat exchangers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a hydrophilizing agent composition for metal capable of hydrophilizing a metal surface of a heat-exchanger fin and the like and sufficiently suppressing color change of a hydrophilized film.SOLUTION: There is provided a hydrophilizing agent composition for metal comprising a poly(meth)acrylic acid-based polymer. In the poly(meth)acrylic acid-based polymer, 10 to 90 mol% of carboxyl groups are neutralized with a secondary amine and / or a tertiary amine based on 100 mol% of all carboxyl groups of the polymer, and a phosphorus element content in the hydrophilizing agent composition for metal is 1.0 to 15 mass% in terms of sodium hypophosphite, based on 100 mass% of the poly(meth)acrylic acid-based polymer before neutralization.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a hydrophilic agent composition for metals. More specifically, it relates to a hydrophilic agent composition for metals useful for fins in heat exchangers and the like. [Background technology]

[0002] Heat exchangers in air conditioners and other similar devices typically have fins that are closely spaced to facilitate heat exchange. In such heat exchangers, condensed water generated during cooling forms water bridges between the fins, leading to problems such as water splashing and increased airflow resistance due to narrowed air passages. Conventionally, the surface of the fin material has been treated to make it hydrophilic in order to suppress the formation of water droplets and the bridges they form. One method of hydrophilization treatment involves the development of a hydrophilic resin. For example, Patent Document 1 discloses a water-soluble resin used in a coating composition for heat exchangers or components for heat exchangers, which is a copolymer of 3-alyloxy-2-hydroxy-1-propanesulfonic acid (HAPS) or a salt thereof and acrylic acid or a salt thereof, characterized in that the ratio of constituent units of HAPS or its salt to 100 mol% of the total monomer constituent units in the copolymer is 23 mol% or more, the average molecular weight of the copolymer is 50,000 or more, and the product of the ratio and the average molecular weight is 3,000,000 or more and 5,000,000 or less. Patent Document 2 discloses a hydrophilic treatment composition for heat exchanger fin material, characterized in that it contains (A) polyvinyl alcohol having a degree of saponification of 87% or more and (B) a neutralized resin in which at least a portion of the carboxyl groups of a high acid value acrylic resin having a resin acid value of 300 mg KOH / g or more form a salt with a basic compound that does not have a boiling point below 180°C and does not decompose below 180°C.

[0003] Furthermore, regarding hydrophilic resins, Patent Document 3 discloses an aqueous solution containing a poly(meth)acrylic acid polymer, wherein at least a portion of the carboxyl groups of the poly(meth)acrylic acid polymer are neutralized with a secondary amine and / or a tertiary amine, the molar ratio of structural units derived from (meth)acrylic acid (salt) to structural units derived from a secondary amine (salt) or tertiary amine (salt) in the aqueous solution is 100:10 to 100:120, and the concentration of inorganic anions containing sulfur atoms or phosphorus atoms in the aqueous solution is 1000 to 30000 ppm relative to the aqueous solution. Patent Document 4 discloses a curable aqueous composition comprising (a) a polyacid containing at least two carboxylic acid groups, acid anhydride groups, or salts thereof; (b) a polyol containing at least two hydroxyl groups; and (c) a phosphorus(III) content enhancer, wherein the ratio of the equivalents of the carboxylic acid groups, acid anhydride groups, or salts thereof to the equivalents of the hydroxyl groups is about 1 / 0.01 to about 1 / 3, and the carboxylic acid groups, acid anhydride groups, or salts thereof are neutralized with a nonvolatile base to a range of about 35% or less. Patent Document 5 discloses a polymer composition comprising a poly(meth)acrylic acid polymer and a bisulfite(salt) adduct to (meth)acrylic acid(salt), wherein the poly(meth)acrylic acid polymer has a sulfonic acid(salt) group at the end of its main chain, has a weight-average molecular weight of 500 to 1,000,000, and the content of the bisulfite(salt) adduct to (meth)acrylic acid(salt) is 0.5 to 15 parts by mass per 100 parts by mass of the total amount of poly(meth)acrylic acid polymer contained in the polymer composition. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2012-122052 [Patent Document 2] Japanese Patent Publication No. 2001-329377 [Patent Document 3] Japanese Patent Publication No. 2013-177534 [Patent Document 4] Japanese Patent Application Publication No. 6-184285 [Patent Document 5] International Publication No. 2013 / 031890 [Overview of the project] [Problems that the invention aims to solve]

[0005] As mentioned above, various hydrophilic treatment compositions for heat exchanger fins and the like have been developed. However, conventional hydrophilic treatment compositions have problems with at least one of the following: heat resistance, discoloration of the coating (film) when applied to and heated on metal surfaces such as heat exchanger fins, the degree of hydrophilicity, or coating adhesion.

[0006] This invention has been made in view of the above-mentioned circumstances, and aims to provide a hydrophilic treatment composition for metals that can hydrophilize metal surfaces such as heat exchanger fins, has excellent coating adhesion, and can sufficiently suppress discoloration of the hydrophilic coating. [Means for solving the problem]

[0007] The inventors of the present invention have conducted various studies on hydrophilic treatment compositions for heat exchanger fins and the like, and have found that by using a composition containing a predetermined amount of carboxyl groups neutralized by a secondary amine and / or tertiary amine in a poly(meth)acrylic acid polymer, and having a phosphorus element content within a predetermined range, metal surfaces can be made hydrophilic, exhibiting excellent coating adhesion and sufficiently suppressing discoloration of the hydrophilic coating. This has led the inventors to the present invention, as they have realized that the above problems can be successfully solved.

[0008] In other words, the first aspect of the present invention is a metal hydrophilizing agent composition comprising a poly(meth)acrylic acid polymer, wherein 5 to 90 mol% of the carboxyl groups of the poly(meth)acrylic acid polymer are neutralized with a secondary amine and / or tertiary amine relative to 100 mol% of the total carboxyl groups of the polymer, and the phosphorus content in the metal hydrophilizing agent composition is 0.1 to 15% by mass relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization, in terms of sodium hypophosphite.

[0009] The above-mentioned hydrophilic agent composition for metals preferably contains a phosphorus compound not bound to the (meth)acrylic acid polymer in an amount of 0.1 to 15% by mass, in terms of sodium hypophosphite, relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization.

[0010] The second aspect of the present invention is a metal hydrophilic agent composition comprising a poly(meth)acrylic acid polymer, wherein 5 to 90 mol% of the carboxyl groups of the poly(meth)acrylic acid polymer are neutralized with a secondary amine and / or a tertiary amine based on 100 mol% of the total carboxyl groups of the polymer, and the phosphorus content in the metal hydrophilic agent composition is 0.1 to 15% by mass based on 100% by mass of the solid content in the composition, calculated as sodium hypophosphite.

[0011] The above-mentioned hydrophilic agent composition for metals preferably contains a phosphorus compound not bonded to a (meth)acrylic acid polymer in an amount of 0.1 to 15% by mass, calculated as sodium hypophosphite, relative to 100% by mass of the solid content in the composition.

[0012] The above poly(meth)acrylic acid polymer preferably has groups derived from hypophosphorous acid and / or its salts.

[0013] The above secondary amine and / or tertiary amine is preferably an alkanolamine.

[0014] The above poly(meth)acrylic acid polymer preferably has a structural unit derived from (meth)acrylic acid and / or its salt in an amount of 80 mol% or more based on 100 mol% of all the structural units.

Advantages of the Invention

[0015] The metal hydrophilizing agent composition of the present invention has the above-described configuration, can hydrophilize the metal surface, and can sufficiently suppress the discoloration of the hydrophilic film. Therefore, it can be suitably used for fin materials such as heat exchangers.

Embodiments for Carrying Out the Invention

[0016] Preferred embodiments of the present invention will be specifically described below. However, the present invention is not limited to the following description and can be appropriately modified and applied without changing the gist of the present invention. The present invention will be described in detail below. When simply referred to as "the present invention" in this specification, it means matters common to the first and second present inventions. A form in which two or more of the individual preferred forms of the present invention described below are combined also falls within the scope of the preferred forms of the present invention.

[0017] ≪Metal hydrophilizing agent composition≫ The metal hydrophilizing agent composition of the first aspect of the present invention contains a poly(meth)acrylic acid polymer in which 5 to 90 mol% of the total carboxyl groups are neutralized by a secondary amine and / or a tertiary amine, and the content of phosphorus element is 0.1 to 15 mass% based on 100 mass% of the poly(meth)acrylic acid polymer before neutralization in terms of sodium hypophosphite. The metal hydrophilizing agent composition of the second aspect of the present invention contains a poly(meth)acrylic acid polymer in which 5 to 90 mol% of the total carboxyl groups are neutralized by a secondary amine and / or a tertiary amine, and the content of phosphorus element is 0.1 to 15 mass% based on 100 mass% of the solid content in the composition in terms of sodium hypophosphite. With such a configuration, the metal surface can be hydrophilized with a hydrophilic film having excellent coating film adhesion, and discoloration of the hydrophilic film can be sufficiently suppressed.

[0018] In the first invention, the lower limit of the content of the phosphorus element is preferably 0.2% by mass, more preferably 0.3% by mass, still more preferably 1.5% by mass, even more preferably 2.0% by mass, and particularly preferably 2.5% by mass. The upper limit is preferably 12% by mass, more preferably 10% by mass, and particularly preferably 8% by mass. The content of the phosphorus element in the hydrophilic agent composition for metal can be measured by the method described in the examples. The amount of the poly(meth)acrylic acid-based polymer before neutralization in the hydrophilic agent composition for metal can be calculated from the area of RI by using gel permeation chromatography (GPC) and preparing a calibration curve using standard polyacrylic acid.

[0019] In the second invention, it is also preferable that the content of the phosphorus element in the hydrophilic agent composition for metal is 0.1 to 15% by mass based on 100% by mass of the solid content in the composition in terms of sodium hypophosphite. The lower limit of the content is more preferably 0.2% by mass, further preferably 0.3% by mass, still more preferably 1.5% by mass, even more preferably 2.0% by mass, and particularly preferably 2.5% by mass. The upper limit is more preferably 12% by mass, further preferably 10% by mass, and particularly preferably 8% by mass. The form in which the carbon numbers of the secondary amine and the tertiary amine are 2 to 10 and the content of the phosphorus element is 0.1 to 1十五% by mass based on 100% by mass of the solid content in the composition is one of the preferred embodiments of the present invention.

[0020] The form of the phosphorus element contained in the hydrophilic agent composition for metal is not particularly limited, and the phosphorus atom may be bonded to the poly(meth)acrylic acid-based polymer, or a phosphorus atom-containing compound or an ion containing a phosphorus atom may be contained in the composition as a component other than the poly(meth)acrylic acid-based polymer.

[0021] In the first aspect of the present invention, the content of free phosphorus elements (phosphorus compounds not bound to the (meth)acrylic acid polymer) in the above-mentioned hydrophilizing agent composition for metals is preferably 0.1 to 15% by mass, in terms of sodium hypophosphite, relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization. The lower limit of the content is more preferably 0.2% by mass, even more preferably 0.3% by mass, and particularly preferably 0.5% by mass. The upper limit is more preferably 12% by mass, even more preferably 10% by mass, and particularly preferably 8% by mass.

[0022] In the second aspect of the present invention, the content of free phosphorus elements (phosphorus compounds not bound to the (meth)acrylic acid polymer) in the above-mentioned hydrophilic agent composition for metals is preferably 0.1 to 15% by mass based on sodium hypophosphite, relative to 100% by mass of solids in the composition. The lower limit of the content is more preferably 0.2% by mass, even more preferably 0.3% by mass, and particularly preferably 0.5% by mass. The upper limit is more preferably 12% by mass, even more preferably 10% by mass, and particularly preferably 8% by mass.

[0023] In the metal hydrophilizing agent composition of the present invention, it is preferable that the phosphorus atom-containing groups, phosphorus atom-containing compounds, and phosphorus atom-containing ions bonded to the polymer are reducing agents. This effectively suppresses the decomposition of the polymer and other components in the composition when heated, thereby further improving the colorfastness (resistance to heat-induced yellowing) of the composition.

[0024] Examples of phosphorus atom-containing groups having the above-mentioned reducing properties include hypophosphorous acid (salt) groups and phosphite (salt) groups. More preferably, hypophosphorous acid (salt) groups are used. Note that hypophosphorous acid (salt) groups and phosphite (salt) groups refer to groups obtained by removing at least one active hydrogen atom from hypophosphorous acid (salt) or phosphite (salt), respectively. Examples of phosphorus atom-containing compounds having the above-mentioned reducing properties include hypophosphorous acid (salt) and phosphorous acid (salt). Hypophosphorous acid (salt) is more preferred. Examples of ions containing phosphorus atoms that have the above-mentioned reducing properties include hypophosphate ions and phosphite ions, with hypophosphate ions being preferred.

[0025] When hypophosphorous acid (salt) groups are bonded to the above poly(meth)acrylic acid polymer, the hypophosphorous acid (salt) groups within the polymer molecule can be introduced into the polymer molecule by polymerizing monomer components containing (meth)acrylic acid (salt) using hypophosphorous acid (salt) as a chain transfer agent, as described later.

[0026] Examples of the salts mentioned above include metal salts, ammonium salts, and organic amine salts. More specifically, metal salts include alkali metal salts such as sodium salts and potassium salts; alkaline earth metal salts such as magnesium salts, calcium salts, strontium salts, and barium salts; and salts such as aluminum salts and iron salts. Examples of organic amine salts include alkanolamine salts such as monoethanolamine salt, diethanolamine salt, and triethanolamine salt; alkylamine salts such as monoethylamine salt, diethylamine salt, and triethylamine salt; and morpholine salts. Among these, sodium salts and potassium salts are preferred.

[0027] If the above-mentioned hydrophilic agent composition for metals contains phosphorus elements other than those bonded to a poly(meth)acrylic acid polymer, it is preferable that it contains hypophosphorous acid and / or its salt (hereinafter also referred to as hypophosphorous acid (salt)). In the first aspect of the present invention, the total content of hypophosphorous acid and / or its salt is preferably 0.1 to 15% by mass relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization. The lower limit of the content is more preferably 0.2% by mass, even more preferably 0.3% by mass, and particularly preferably 0.5% by mass. The upper limit is more preferably 12% by mass, even more preferably 10% by mass, and particularly preferably 8% by mass. In the second aspect of the present invention, the total content of hypophosphorous acid and / or its salt is preferably 0.1 to 15% by mass based on 100% by mass of solids in the composition. The lower limit of the content is more preferably 0.2% by mass, even more preferably 0.3% by mass, and particularly preferably 0.5% by mass. The upper limit is more preferably 12% by mass, even more preferably 10% by mass, and particularly preferably 8% by mass. If the above-mentioned metal hydrophilic agent composition contains hypophosphorous acid (salt), the hypophosphorous acid (salt) in the composition may be, for example, unreacted chain transfer agents remaining from the production of poly(meth)acrylic acid polymers, or it may be added separately.

[0028] The content of the poly(meth)acrylic acid polymer in the above-mentioned metal hydrophilizing agent composition is not particularly limited, but in order to fully exhibit the performance derived from the poly(meth)acrylic acid polymer, it is preferable that it be 85% by mass or more based on 100% by mass of solids in the composition. The lower limit is more preferably 90% by mass, and even more preferably 92% by mass. The upper limit is more preferably 99.9% by mass, and even more preferably 99.5% by mass.

[0029] <Poly(meth)acrylic acid polymer> The above-mentioned poly(meth)acrylic acid polymer has structural units derived from (meth)acrylic acid (salt). This allows for sufficient hydrophilization of metal surfaces. (Meth)acrylic acid (salt) refers to acrylic acid, acrylate salts, methacrylic acid, and methacrylic acid salts. Examples of salts include the metal salts, ammonium salts, and organic amine salts mentioned above.

[0030] The above poly(meth)acrylic acid polymer may have only a structure derived from (meth)acrylic acid (salt), or it may have a structure derived from other monomers copolymerizable with (meth)acrylic acid (salt). Other monomers include, specifically, carboxyl group-containing monomers other than (meth)acrylic acid (salts), such as maleic acid, fumaric acid, itaconic acid, crotonic acid, 2-methylene glutaric acid, and their salts; and hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and α-hydroxymethylethyl (meth)acrylate. Alkyl (meth)acrylates; alkyl (meth)acrylates, which are esters of (meth)acrylic acid with C1 to C18, such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and lauryl (meth)acrylate; amino group-containing acrylates such as dimethylaminoethyl (meth)acrylate or its quaternary derivatives; amide group-containing monomers such as (meth)acrylamide, dimethylacrylamide, and isopropylacrylamide;

[0031] Vinyl esters such as vinyl acetate; alkenes such as ethylene and propylene; aromatic vinyl monomers such as styrene; maleimide derivatives such as maleimide, phenylmaleimide, and cyclohexylmaleimide; nitrile group-containing vinyl monomers such as (meth)acrylonitrile; monomers having sulfonic acid groups such as 3-allyloxy-2-hydroxypropanesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, styrenesulfonic acid, and vinylsulfonic acid, and their salts; monomers having phosphonic acid groups such as vinylphosphonic acid and (meth)allylphosphonic acid; (meth)acrolein, etc. Examples include aldehyde group-containing vinyl monomers; alkyl vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; other functional group-containing monomers such as vinyl chloride, vinylidene chloride, allyl alcohol, and vinylpyrrolidone; and polyalkylene glycol chain-containing monomers such as polyalkylene glycol (meth)acrylate, monoalkoxy polyalkylene glycol (meth)acrylate, vinyl alcohol, (meth)allyl alcohol, and monomers having a structure in which 1 to 300 moles of alkylene oxide are added to unsaturated alcohols such as isoprenol. These other monomers may be used individually or in combination of two or more.

[0032] The above poly(meth)acrylic acid polymer preferably has a proportion of structural units derived from (meth)acrylic acid (salt) of 80 mol% or more, relative to 100 mol% of the total structural units (structural units derived from (meth)acrylic acid (salt) and structural units derived from other monomers). More preferably, it is 90 mol% or more, and even more preferably 95 mol% or more.

[0033] The above poly(meth)acrylic acid polymer preferably has a proportion of structural units derived from other monomers of 20 mol% or less, relative to 100 mol% of the total structural units. More preferably, it is 10 mol% or less, and even more preferably 5 mol% or less.

[0034] The above poly(meth)acrylic acid polymer is obtained in which 5 to 90 mol% of the carboxyl groups, relative to 100 mol% of the total carboxyl groups in the polymer, are neutralized with a secondary amine and / or tertiary amine. This results in a more suitable range of flexibility (elasticity) of the coating film formed using the composition of the present invention. Preferably, the lower limit is 7 mol% or more of carboxyl groups, more preferably 10 mol% or more, and even more preferably 15 mol% or more of carboxyl groups neutralized with a secondary amine and / or tertiary amine. Preferably, the upper limit is 70 mol% or less of carboxyl groups, more preferably 60 mol% or less, and even more preferably 50 mol% or less of carboxyl groups neutralized with a secondary amine and / or tertiary amine.

[0035] The carbon number of the secondary and tertiary amines is preferably 2 to 30. More preferably 2 to 15, and even more preferably 3 to 10.

[0036] The secondary and tertiary amines mentioned above are defined by the following formula (1); NR 1 3(1) (In the formula, R 1 R represents a hydrocarbon group having 1 to 10 carbon atoms, which may have a hydrogen atom or substituents, either identical or different. 1 A compound represented by ( ) is preferred, which is a hydrocarbon group having 1 to 10 carbon atoms, of which at least two may have substituents. The hydrocarbon group has preferably 1 to 8 carbon atoms, more preferably 1 to 6, and even more preferably 2 to 4 carbon atoms. If the hydrocarbon group has substituents, the carbon number includes the carbon atoms of the substituents.

[0037] The hydrocarbon groups mentioned above include methyl group, ethyl group, n-propyl group, n-butyl group, n-pentyl group (amyl group), n-hexyl group, n-heptyl group, n-octyl group, n-nonyl group, n-decyl group, i-propyl group, sec-butyl group, i-butyl group, t-butyl group, 1-methylbutyl group, 1-ethylpropyl group, 2-methylbutyl group, i-amyl group, neopentyl group, 1,2-dimethylpropyl group, 1,1-dimethylpropyl group, t-amyl group, 1,3-dimethylbutyl group, 3,3-dimethylbutyl group, and 2-ethyl Examples include linear or branched alkyl groups such as butyl group, 2-ethyl-2-methylpropyl group, 1-methylheptyl group, 2-ethylhexyl group, 1,5-dimethylhexyl group, t-octyl group, branched nonyl group, and decyl group; cyclic alkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl; and aryl groups such as phenyl group, benzyl group, phenethyl group, o-,m- or p-tolyl group, 2,3- or 2,4-xylyl group, mesityl group, and naphthyl group. Among these, linear or branched alkyl groups are preferred. More preferably are methyl group, ethyl group, n-propyl group, n-butyl group, i-propyl group, sec-butyl group, i-butyl group, and t-butyl group, and even more preferably methyl group, ethyl group, n-propyl group, and i-propyl group.

[0038] The substituents that the hydrocarbon group may have are not particularly limited, but examples include hydroxyl groups, alkoxy groups, carboxyl groups, acyl groups, sulfonic acid groups, amino groups, phosphate groups, ether groups, thioether groups, carbonyl groups, and ester groups. Preferably, the substituents are hydroxyl groups, carboxyl groups, sulfonic acid groups, amino groups, and phosphate groups. Such reactive substituents can form crosslinked structures with reactive functional groups such as carboxyl groups of the polymer, thereby further improving the strength of the coating film. Hydroxyl groups are more preferred as substituents. The above R 1 Preferably, at least one of them is a hydrocarbon group having a hydroxyl group. More preferably R 1 Two or three of these are hydrocarbon groups having hydroxyl groups, and more preferably R1 Two of these are hydrocarbon groups that have a hydroxyl group.

[0039] The above secondary amines are not particularly limited, but examples include aliphatic monoamines such as dimethylamine, diethylamine, dipropylamine, diisopropylamine, N-methylethylamine, N-methylpropylamine, N-methylisopropylamine, N-methylbutylamine, N-methylisobutylamine, N-methylcyclohexylamine, N-ethylpropylamine, N-ethylisopropylamine, N-ethylbutylamine, N-ethylisobutylamine, N-ethylcyclohexylamine, N-methylvinylamine, N-methylallylamine; aromatic amines such as methylaniline, ethylaniline, N-methylbenzylamine, N-ethylbenzylamine, N-methylphenethylamine, N-ethylphenethylamine; and N-methylethanolamine, N Examples include monoalkanolamines such as ethylethanolamine, N-propylethanolamine, N-isopropylethanolamine, N-butylethanolamine, N-isobutylethanolamine, N-methylpropanolamine, N-ethylpropanolamine, N-propylpropanolamine, N-isopropylpropanolamine, N-butylpropanolamine, and N-isobutylpropanolamine; dialkanolamines such as dimethanolamine, diethanolamine, 2-((hydroxymethyl)amino)ethanol, dipropanolamine, diisopropanolamine, and dibutanolamine; and cyclic amines such as pyrrolidine, piperidine, piperazine, N-methylpiperazine, N-ethylpiperazine, morpholine, and thiomorpholine.

[0040] The above tertiary amines are not particularly limited, but examples include aliphatic monoamines such as trimethylamine, triethylamine, triisopropylamine, tripropylamine, tributylamine, triisobutylamine, tri-sec-butylamine, tripentylamine, dimethylethylamine, diethylmethylamine, dimethylpropylamine, and dipropylmethylamine; aromatic amines such as dimethylaniline, diethylaniline, N,N-dimethylbenzylamine, N,N-diethylbenzylamine, N,N-dimethylphenethylamine, N,N-diethylphenethylamine, and tripenzylamine; and N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dipropylethanolamine, N,N-ethylmethylethanolamine, and N,N-dimethylpropano Examples include monoalkanolamines such as malamine, N,N-diethylpropanolamine, N,N-dipropylpropanolamine, and N,N-ethylmethylpropanolamine; dialkanolamines such as N-methyldiethanolamine, N-ethyldiethanolamine, N-propyldiethanolamine, N-isopropyldiethanolamine, N-butyldiethanolamine, N-isobutyldiethanolamine, N-methyldipropanolamine, N-ethyldipropanolamine, N-propyldipropanolamine, N-isopropyldipropanolamine, N-butyldipropanolamine, and N-isobutyldipropanolamine; and trialkanolamines such as triethanolamine, tripropanolamine, triisopropanolamine, and tributanolamine.

[0041] The above secondary amine and / or tertiary amine is preferably an alkanolamine. The alkanolamine only needs to have at least one hydroxyl group, but is more preferably a dialkanolamine and a trialkanolamine, even more preferably a dialkanolamine, and particularly preferably a diethanolamine.

[0042] In the above poly(meth)acrylic acid polymer, some of the carboxyl groups of the polymer may be neutralized with a secondary amine and / or a tertiary amine, as well as other neutralizing agents. Other neutralizing agents include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate and sodium bicarbonate, alkaline earth metal salts, ammonia, and other organic amines other than secondary and tertiary amines. Other organic amines include primary amines, quaternary derivatives of the above tertiary amines, and polyamines. Primary amines include alkanolamines such as monoethanolamine and monopropanolamine; alkylamines such as methylamine, ethylamine, and butylamine; and ethylenediamine and propylenediamine. Polyamines include, for example, polyalkyleneimines such as polyethyleneimine, polyalkylene polyamines, polyamide polyamines, polyalkyleneimine alkylene oxides, and polyvinylamines. Preferably, polyalkyleneimines are used, and more preferably, polyethyleneimine.

[0043] The poly(meth)acrylic acid polymer described above preferably has the aforementioned reducing phosphorus atom-containing group within its molecule. This allows for more effective suppression of polymer decomposition when the polymer is heated, thereby improving the colorfastness of the composition. The above poly(meth)acrylic acid polymer more preferably has groups derived from hypophosphorous acid and / or its salts. The above poly(meth)acrylic acid polymer is further preferably having a hypophosphorous (salt) group at the main chain end (molecular end). Analysis of phosphorus atom-containing groups in the polymer can be performed, for example, 31 This can be done by P-NMR measurement, etc.

[0044] In the first aspect of the present invention, when the poly(meth)acrylic acid polymer has a phosphorus atom-containing group, the phosphorus atom content in the polymer is preferably 0.1 to 15% by mass, in terms of sodium hypophosphite, relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization. More preferably, the lower limit is 0.3% by mass, and more preferably 0.5% by mass. More preferably, the upper limit is 10% by mass, even more preferably 8% by mass, and particularly preferably 5% by mass. In the second aspect of the present invention, when the poly(meth)acrylic acid polymer has a phosphorus atom-containing group, the phosphorus atom content in the polymer is preferably 0.1 to 15% by mass, in terms of sodium hypophosphite, based on 100% by mass of the solid content in the composition. More preferably, the lower limit is 0.3% by mass, and more preferably 0.5% by mass. More preferably, the upper limit is 10% by mass, even more preferably 8% by mass, and particularly preferably 5% by mass. The content of phosphorus atom-containing groups in the above polymer is, for example, 31 It can be measured by PNMR analysis.

[0045] The above poly(meth)acrylic acid polymer preferably has a weight-average molecular weight of 1,000 to 1,000,000. More preferably, the lower limit is 2,000 or more, even more preferably 3,000 or more, and particularly preferably 4,000 or more. More preferably, the upper limit is 500,000 or less, even more preferably 100,000 or less, even more preferably 50,000 or less, even more preferably 30,000 or less, and particularly preferably 20,000 or less. The above weight-average molecular weight can be measured by the method described in the examples.

[0046] <Methacryloyl (meth)acrylic acid polymer production method> The method for producing the above-mentioned poly(meth)acrylic acid polymer is not particularly limited, but it can be produced by polymerizing monomer components containing (meth)acrylic acid (salt). Specific examples and preferred examples of monomer components, as well as preferred proportions of each monomer, are as described above.

[0047] (Polymerization process) The method for initiating the polymerization of monomer components in the above polymerization process is not particularly limited, but examples include adding a polymerization initiator, irradiating with UV light, applying heat, or irradiating with light in the presence of a photoinitiator. In the polymerization process described above, it is preferable to use a polymerization initiator.

[0048] Examples of polymerization initiators include hydrogen peroxide; persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate; dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. Suitable polymerization initiators include azo compounds such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride and 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride; organic peroxides such as benzoyl peroxide, lauroyl peroxide, peracetic acid, di-t-butyl peroxide, and cumenehydroperoxide; and redox initiators that generate radicals by combining an oxidizing agent and a reducing agent, such as ascorbic acid and hydrogen peroxide, or persulfates and metal salts. Of these polymerization initiators, hydrogen peroxide, persulfates, and azo compounds are preferred, with persulfates being the most preferred, as they tend to reduce the amount of residual monomers. These polymerization initiators may be used alone or in the form of a mixture of two or more. The amount of polymerization initiator used is preferably 0.1 g or more and 15 g or less, and more preferably 0.2 g to 12 g, per mole of the total monomer used.

[0049] In the polymerization step described above, a chain transfer agent may be used as needed. Specific examples of chain transfer agents include thiol-based chain transfer agents such as mercaptoethanol and mercaptopropionic acid; halides such as carbon tetrachloride and methylene chloride; secondary alcohols such as isopropyl alcohol and glycerin; hypophosphorous acid (salts) such as hypophosphorous acid and sodium hypophosphorous acid (including their hydrates); phosphorous acid (salts) such as phosphorous acid and sodium phosphite; sulfurous acid (salts) such as sodium sulfite; bisulfite (salts) such as sodium bisulfite; dithionite (salts) such as sodium dithionite; pyrosulfite (salts) such as potassium pyrosulfite; and hydrogen peroxide. Preferably, the above chain transfer agents are hypophosphorous acid (salts), phosphorous acid (salts), bisulfite (salts), hydrogen peroxide, and mercaptopropionic acid, and more preferably, hypophosphorous acid (salts), bisulfite (salts), and hydrogen peroxide. The above chain transfer agents may be used individually or in the form of a mixture of two or more. By using hypophosphorous acid (salt) or phosphite (salt) as a chain transfer agent, the resulting poly(meth)acrylic acid polymer will have hypophosphorous acid (salt) groups or phosphite (salt) groups. Furthermore, these compounds as chain transfer agents may remain unreacted in the metal hydrophilizing agent composition of the present invention. The amount of chain transfer agent used is preferably 0 g or more and 20 g or less per mole of monomer (total monomer) used, and more preferably 0 g or more and 15 g or less.

[0050] In the polymerization process described above, if a solvent is used, an aqueous solvent is preferred. Examples of aqueous solvents include water, alcohols such as methyl alcohol, ethyl alcohol, isopropyl alcohol (2-propanol), n-butyl alcohol, and diethylene glycol, glycols, glycerin, polyethylene glycol, and mixtures thereof, with water being preferred. To improve the solubility of the monomer in the solvent, any suitable organic solvent may be added as needed, provided it does not adversely affect polymerization. Examples of such organic solvents include lower alcohols such as methanol, ethanol, and isopropyl alcohol; lower ketones such as acetone, methyl ethyl ketone, and diethyl ketone; ethers such as dimethyl ether, diethyl ether, and dioxane; and amides such as dimethylformaldehyde. One or more of these solvents may be used. The amount of solvent used is preferably 40 to 400% by mass per 100% by mass of monomer.

[0051] In the polymerization process described above, the polymerization temperature is not particularly limited, but is preferably 20°C to 110°C, more preferably 40°C to 105°C, and even more preferably 50°C to 105°C. Furthermore, the reaction time should be set appropriately according to the reaction temperature, the type (properties) and combination of monomer components, polymerization initiator, and solvent, as well as the amount used, so that the polymerization reaction is completed.

[0052] The above polymer production method preferably includes a maturation step after the polymerization reaction. The maturation step is a step in which the reaction mixture is kept within a certain temperature range after the addition of raw materials to the reactor is complete, in order to promote the reaction of the polymer raw materials and reduce the amount of residue. The temperature in the above maturation step is not particularly limited, but is preferably 50 to 105°C. The maturation time in the above maturation step is not particularly limited, but is preferably 10 minutes to 5 hours. More preferably 20 minutes to 3 hours.

[0053] (neutralization process) The poly(meth)acrylic acid polymer (aqueous solution) of the present invention is preferably produced by a step of neutralizing an aqueous solution containing an acidic type and / or partially neutralized type poly(meth)acrylic acid polymer with a secondary amine and / or tertiary amine (or a step of adding a secondary amine and / or tertiary amine to an aqueous solution containing an acidic type and / or partially neutralized type poly(meth)acrylic acid polymer).

[0054] When the poly(meth)acrylic acid polymer (aqueous solution) of the present invention is manufactured by a step of neutralizing with the secondary amine and / or tertiary amine, other neutralizing agents may be used in addition to the secondary amine and / or tertiary amine. These neutralizing agents may be added before the polymerization step, during polymerization, during the aging step, or after the aging step, for purposes such as adjusting the pH and reaction rate. On the other hand, it is preferable to add them after the aging step in order to reduce discoloration during the neutralization reaction. When using other neutralizing agents in addition to the secondary amine and / or tertiary amine, it is preferable to first perform a step of neutralizing an aqueous solution containing the acidic type and / or partially neutralized type poly(meth)acrylic acid polymer with the other neutralizing agent (hereinafter also referred to as step N1), and then perform a step of neutralizing the aqueous solution containing the acidic type and / or partially neutralized type poly(meth)acrylic acid polymer with the secondary amine and / or tertiary amine (hereinafter also referred to as step N2), as this results in a better color tone, but the reverse order of the steps is also possible.

[0055] The temperatures for the above N1 and N2 steps are not particularly limited, but are preferably 40 to 100°C, more preferably 45 to 95°C, and especially preferably 50 to 90°C. The time required for the above N1 and N2 steps can be appropriately selected depending on the type and amount of neutralizing agent used, but generally, 10 hours or less is preferred, 5 hours or less is more preferred, and 3 hours or less is even more preferred.

[0056] <Other components in the metal hydrophilizing agent composition> The metal hydrophilizing agent composition of the present invention may contain other components besides poly(meth)acrylic acid polymers, phosphorus atom-containing compounds, and phosphorus atom-containing ions. Other components include solvents; cationic components such as sodium ions and ammonium ions; anionic components such as chloride ions and sulfate ions; unreacted monomers; polymerization inhibitors such as hydroquinone and methoquinone; nonamine polyol compounds having at least two hydroxyl groups, such as polyols like ethylene glycol, propylene glycol, glycerol, and trimethylolpropane, and their alkylene glycol adducts; sugars such as erythritol, pentaerythritol, treitol, arabinitol, xylitol, ribitol, iditol, galactitol, sorbitol, mannitol, boremitol, perseitol, and D-erythro-D-galacto-octitol, and their alkylene glycol adducts; and the like.

[0057] The content of other components in the above-mentioned hydrophilic agent composition for metals is not particularly limited, but is preferably 10% by mass or less per 100% by mass of the composition. More preferably 5% by mass or less, and even more preferably 3% by mass or less.

[0058] <Paint composition> The above-mentioned hydrophilic agent composition for metals is preferably used as a paint composition for metals. The amount of the above-mentioned hydrophilic agent composition for metals included in the paint composition is appropriately set considering hydrophilicity, paintability, etc., but is preferably 0.1 to 50% by mass in terms of solid content concentration.

[0059] The above paint composition may also contain other components besides poly(meth)acrylic acid polymers, phosphorus atom-containing compounds, and phosphorus atom-containing ions. The other components are not particularly limited. For example, water-soluble resins other than poly(meth)acrylic acid-based polymers such as cellulose-based polymers, polyvinyl alcohol-based polymers, and polyethylene glycol; crosslinking agents such as melamine resins, urea resins, phenol resins, polyepoxy compounds, blocked polyisocyanate compounds, and metal chelate compounds such as titanium chelate; surfactants; colloidal silica; antibacterial agents; coloring pigments; rust-preventive pigments; rust inhibitors; solvents and the like can be mentioned.

[0060] ≪Method for hydrophilizing metal surface≫ The present invention is also a method for hydrophilizing the surface of a metal such as a fin material of a heat exchanger using the hydrophilizing agent composition for metal of the present invention. The above hydrophilizing method preferably includes a step of coating the hydrophilizing agent composition for metal on the metal surface and a step of heating and drying. The coating amount (formation amount) of the hydrophilizing agent composition for metal in the above coating step is not particularly limited, but 10 to 20000 mg / m 2 is preferable.

[0061] The heating temperature in the above heating and drying step is not particularly limited, but 80 to 250°C is preferable. The heating time is not particularly limited, but 0.01 to 30 minutes is preferable. The film thickness of the coating film formed by the above hydrophilizing treatment is not particularly limited, but 0.02 to 10 μm is preferable, and more preferably 0.1 to 5 μm.

[0062] The metal on which the above hydrophilizing treatment is performed is not particularly limited, but aluminum or an aluminum alloy is preferable. Examples of the aluminum alloy include aluminum alloys such as 1100, 1200, 1050, 3003, 7072, etc. according to the alloy number of the JIS standard. It is preferable that the surface of the above metal is subjected to chemical conversion treatment from the viewpoints of the adhesion and corrosion resistance of the hydrophilic treatment film. Examples of the above chemical conversion treatment include chromate treatment. Specifically, treatment methods such as the alkali salt-chromate method (B.V. method, M.B.V. method, E.W. method, Allroc method, Pirmin method), chromic acid method, chromate method, phosphoric acid chromic acid method, and the anhydrous coating type treatment method using a composition mainly composed of chromate are included.

Examples

[0063] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to only these examples. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0064] <Measurement conditions for weight average molecular weight> The weight average molecular weight of the polymer was measured using gel permeation chromatography (GPC) under the following conditions. Apparatus: HLC-8320GPC manufactured by Tosoh Corporation Detector: RI Columns: Two TSKgel guardcolumns, G3000PWXL (manufactured by Tosoh Corporation) were connected in this order from the sample inlet. Column temperature: 40 °C Flow rate: 0.5 ml / min Standard substance for calibration curve preparation: Sodium polyacrylate standard sample manufactured by American Polymer Standards (7 types with peak top molecular weight (Mp) between 900 and 475,000) Calibration curve: Cubic equation based on the Mp value and elution time of the above standard substance Eluent: 0.08 M phosphate buffer

[0065] <pH measurement> The pH of the copolymer composition was measured under the following conditions. Apparatus: pH METER D-52 manufactured by HORIBA Electrode: Glass electrode Temperature: 25 °C

[0066] <Measurement of phosphorus atom-containing group content in polymers and metal hydrophilic agent compositions> The phosphorus atom-containing group content in the polymer was calculated from the amount of phosphorus atom-containing groups at the start of the process and the amount of free phosphorus atom-containing groups. The amount of free phosphorus atom-containing groups was measured using anion chromatography under the following conditions. Equipment: Tosoh Ion Chromatography System IC-2010 Detector: RI Columns: SHODEX IC SI-90G and SHODEX IC SI-90 4E are connected in this order from the sample inlet. Column temperature: 25℃ Flow rate: 1.2ml / min Standard substances for calibration curve creation: Reagents containing the ion species to be measured. For example, a calibration curve for hypophosphate ions can be created using sodium hypophosphate monohydrate manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., a calibration curve for phosphite ions can be created using phosphorous acid manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and a calibration curve for phosphate ions can be created using phosphoric acid manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Eluent: 0.1 wt% sodium bicarbonate aqueous solution Sample preparation: The sample was prepared by diluting it with the eluent.

[0067] <Measurement of solid content> Approximately 1.2 g of the sample was weighed into an aluminum dish, diluted with approximately 1 g of water, and spread evenly. This was dried in a 130°C oven for 1 hour, then cooled in a desiccator, and the mass was measured after drying. The solid content (non-volatile content) concentration was calculated from the difference in mass before and after drying. Unless otherwise specified, the solid content measured using the above procedure was used as the concentration of the metal hydrophilizing agent composition and the aqueous solution of poly(meth)acrylic acid polymer.

[0068] <Creation of coating film> A hydrophilic coating was created on the aluminum plate using the following procedure. Dryer: Automatic discharge dryer ATO101 manufactured by Tojo Thermal Engineering Co., Ltd. Baking conditions: 220°C, 10 seconds A paint composition precursor was prepared by adding a hydrophilic agent composition, deionized water, a 4% polyvinyl alcohol aqueous solution, and a 5% polyethylene glycol aqueous solution to a 20 mL glass container with a lid, so that the solid content ratio of polyacrylic acid, polyvinyl alcohol, and polyethylene glycol was 20 / 40 / 40, and the total solid content of the three components was 5%. To the prepared paint composition precursor, 5% butyl cellosolve was added relative to the total solid content of the paint liquid precursor to prepare the paint composition. The prepared coating composition was applied to a chromate-treated aluminum plate using a bar coater and immediately dried in a 220°C dryer for 10 seconds. Afterward, it was air-cooled at room temperature to obtain a hydrophilic coating film on the aluminum plate.

[0069] <Evaluation of hydrophilicity of coating film> The hydrophilicity of the coating film was evaluated by measuring the water contact angle using the following method. Equipment: Contact angle meter DM500 manufactured by Kyowa Interface Science Co., Ltd. Measurement method: θ / 2 method As a pretreatment, the prepared coating film was immersed in deionized water at room temperature for 15 minutes and allowed to air dry. A 1.0 μL droplet of deionized water was prepared using a dispenser and dropped onto the hydrophilic coating film. The contact angle was measured 30 seconds after droplet placement.

[0070] <Heat resistance (color resistance) evaluation> The heat resistance of the coating film was evaluated by the degree of coloration of the coating film after heat treatment using the following method. Dryer: Yamato Scientific Co., Ltd. DNF400 constant temperature incubator with forced airflow Color difference meter: Spectroscopic color meter SE-6000 manufactured by Nippon Denshoku Industries Co., Ltd. The prepared coating film was placed in a dryer heated to 170°C and stored at 170°C for 1 hour. After removing it from the dryer, it was air-cooled at room temperature. The color difference of the coating film was measured, and those with a Hazen value exceeding 200 were judged to have poor heat resistance.

[0071] <Evaluation of coating adhesion> The adhesion of the coating film was evaluated using the following method. As a pretreatment, the prepared coating film was immersed in deionized water at room temperature for 15 minutes and allowed to air dry. The coating film was secured with tape to prevent movement, 10 μL of deionized water was dropped onto the surface, and a 500g weight was placed on top. The surface of the weight was covered with Kimwipes® (manufactured by Nippon Paper Crecia Co., Ltd.), and the weight was secured so that Kimwipes® (manufactured by Nippon Paper Crecia Co., Ltd.) was sandwiched between the coating film and the weight. The weight was vibrated 15 times horizontally to the coating film at a speed of 30 rpm, and the degree of coating film peeling was evaluated visually. If the coating film peeled off and the luster of the aluminum was visible, it was judged that the adhesion of the coating film was poor.

[0072] <Example 1> 362.7g of pure water was pre-charged into a 2.5L stainless steel separable flask equipped with a stirrer, reflux condenser, and thermometer, and the temperature was raised to the boiling point under stirring. Then, under stirring, 900.0g of 80% acrylic acid (hereinafter abbreviated as AA) aqueous solution, 257.3g of pure water, 79.3g of 45% sodium hypophosphate monohydrate (hereinafter abbreviated as SHP) aqueous solution, and 50.1g of 15% sodium persulfate (hereinafter abbreviated as NaPS) aqueous solution were added dropwise separately to the system under reflux at the boiling point. The entire 80% AA aqueous solution was added dropwise at a constant rate from 0 to 180 minutes. The entire pure water was added dropwise at a constant rate from 92 to 180 minutes. 13.9g of the 45% SHP aqueous solution was added dropwise from 0 to 18 minutes, and the remaining 65.4g was added dropwise from 18 to 210 minutes under a constant rate. The entire 15% NaPS aqueous solution was added dropwise from 0 to 195 minutes at a constant dropping rate. After all additions were complete, the mixture was matured for another 30 minutes under reflux conditions to complete the polymerization and obtain a polyacrylic acid polymer (1). After cooling to below 70°C, 433.7 g of 80% diethanolamine (hereinafter abbreviated as DEA) aqueous solution and 76.2 g of 45% SHP aqueous solution were added to obtain a metal hydrophilizing agent composition (1). In the above operating time, the time at which the addition of monomers such as acrylic acid began to be added to the reactor after heating was defined as 0 minutes (the same applies to the following examples and comparative examples).

[0073] <Example 2> The same procedure as in Example 1 was followed, except that the addition of the 45% SHP aqueous solution after maturation was omitted, to obtain a metal hydrophilizing agent composition (2).

[0074] <Example 3> The same procedure as in Example 1 was followed, except that the amount of 80% DEA aqueous solution added after maturation was 262.9 g, and the addition of 45% SHP aqueous solution after maturation was omitted, to obtain a metal hydrophilizing agent composition (3).

[0075] <Example 4> The same procedure as in Example 1 was followed, except that the amount of 80% DEA aqueous solution added after maturation was 131.4 g, and the addition of 45% SHP aqueous solution after maturation was omitted, to obtain a metal hydrophilizing agent composition (4).

[0076] <Example 5> 638.5 g of pure water was pre-charged into a 2.5 L stainless steel separable flask equipped with a stirrer, reflux condenser, and thermometer, and the temperature was raised to the boiling point under stirring. Then, under stirring, 144.4 g of 80% AA aqueous solution, 158.9 g of pure water, and 58.1 g of 15% NaPS aqueous solution were added dropwise separately to the system under reflux at the boiling point. The entire 80% AA aqueous solution was added dropwise at a constant rate from 0 to 180 minutes. The entire pure water was added dropwise at a constant rate from 0 to 170 minutes. The entire 15% NaPS aqueous solution was added dropwise at a constant rate from 0 to 185 minutes. After all additions were completed, the system was maintained under reflux at the boiling point for another 60 minutes to complete the polymerization. Subsequently, the mixture was concentrated under reduced pressure to obtain polyacrylic acid polymer (2) with a solid content of 45%. After cooling the obtained polymer aqueous solution to below 70°C, 69.6 g of 80% DEA aqueous solution and 26.5 g of 45% SHP aqueous solution were added to obtain metal hydrophilizing agent composition (5).

[0077] <Example 6> 321.4g of pure water was pre-charged into a 2.5L stainless steel separable flask equipped with a stirrer, reflux condenser, and thermometer, and the temperature was raised to 90°C under stirring. Then, under stirring, 675.0g of 80% AA aqueous solution, 31.3g of 48% sodium hydroxide aqueous solution, 90.0g of 15% NaPS aqueous solution, and 82.4g of 35% sodium bisulfite were added dropwise to the 90°C system separately. The 80% AA aqueous solution and the 48% sodium hydroxide aqueous solution were added continuously at a constant dropping rate from 0 to 180 minutes. The 15% NaPS aqueous solution was added continuously at a constant dropping rate from 0 to 185 minutes. 14.4g of 35% sodium bisulfite was added continuously at a constant dropping rate from 0 to 18 minutes, and the remaining 68.0g was added continuously at a constant dropping rate from 18 to 210 minutes. After all the dropwise addition was complete, the polymerization was completed by maintaining the temperature at 90°C for another 30 minutes to obtain a polyacrylic acid-based polymer (3). After cooling the obtained polymer aqueous solution to below 70°C, 325.3 g of 80% DEA aqueous solution and 116.8 g of 45% SHP aqueous solution were added to obtain a metal hydrophilizing agent composition (6).

[0078] <Example 7> The same procedure as in Experimental Example 2 was followed, except that the amount of 45% SHP aqueous solution added after maturation was changed to 56.2 g, to obtain a metal hydrophilizing agent composition (7).

[0079] <Comparative Example 1> The same procedure as in Example 1 was followed, except that the addition of the 80% DEA aqueous solution and the 45% SHP aqueous solution after maturation was omitted, to obtain a metal hydrophilizing agent composition (8).

[0080] <Comparative Example 2> The same procedure as in Example 5 was followed, except that the addition of the 80% DEA aqueous solution and the 45% SHP aqueous solution after vacuum concentration was omitted, to obtain a metal hydrophilizing agent composition (9).

[0081] <Comparative Example 3> Except for adding 21.1 g of the 80% DEA aqueous solution after vacuum concentration and omitting the addition of the 45% SHP aqueous solution, the same procedure as in Example 5 was performed to obtain a metal hydrophilizing agent composition (10).

[0082] <Comparative Example 4> The same procedure as in Example 5 was followed, except that the amount of 80% DEA added after vacuum concentration was 42.2 g, and the addition of 45% SHP was omitted, to obtain a metal hydrophilizing agent composition (11).

[0083] <Comparative Example 5> The same procedure as in Example 5 was followed, except that the addition of 45% SHP after vacuum concentration was omitted, to obtain a metal hydrophilizing agent composition (12).

[0084] The hydrophilic agent compositions for metals obtained in Examples 1-7 and Comparative Examples 1-5 were evaluated for coating adhesion, hydrophilicity of the coating film, and heat resistance (discoloration resistance). The results are shown in Table 1.

[0085] [Table 1]

Claims

1. A hydrophilizing agent composition for metals containing a poly(meth)acrylic acid polymer, The poly(meth)acrylic acid polymer has 5 to 90 mol % of carboxyl groups neutralized with a secondary amine and / or a tertiary amine, based on 100 mol % of all carboxyl groups in the polymer; a content of phosphorus in the metal hydrophilizing agent composition, calculated as sodium hypophosphite, of 0.1 to 15% by mass relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization.

2. The hydrophilizing agent composition for metals according to claim 1, characterized in that the hydrophilizing agent composition for metals contains, in terms of sodium hypophosphite, 0.1 to 15% by mass of a phosphorus compound that is not bonded to the (meth)acrylic acid polymer, relative to 100% by mass of the poly(meth)acrylic acid polymer before neutralization.

3. A hydrophilizing agent composition for metals containing a poly(meth)acrylic acid polymer, The poly(meth)acrylic acid polymer has 5 to 90 mol % of carboxyl groups neutralized with a secondary amine and / or a tertiary amine, based on 100 mol % of all carboxyl groups in the polymer; a content of elemental phosphorus in the metal hydrophilizing agent composition, calculated as sodium hypophosphite, of 0.1 to 15 mass% relative to 100 mass% of the solid content in the composition;

4. The hydrophilizing agent composition for metals according to claim 3, characterized in that the hydrophilizing agent composition for metals contains a phosphorus compound that is not bonded to the (meth)acrylic acid-based polymer in an amount of 0.1 to 15 mass% in terms of sodium hypophosphite relative to 100 mass% of the solids content of the composition.

5. 5. The metal hydrophilizing agent composition according to claim 1, wherein the poly(meth)acrylic acid polymer has a group derived from hypophosphorous acid and / or a salt thereof.

6. 6. The metal hydrophilizing agent composition according to claim 1, wherein the secondary amine and / or the tertiary amine is an alkanolamine.

7. The metal hydrophilizing agent composition according to any one of claims 1 to 6, wherein the poly(meth)acrylic acid polymer has structural units derived from (meth)acrylic acid and / or a salt thereof in an amount of 80 mol % or more relative to 100 mol % of all structural units.